The Effect Of Service Quality, Customer Values, And Customer Relationship Management (Crm) On Customer Loyalty At Jne Express Plamo Garden - Ananda, Defi; Satriawan, Bambang; Windayati, Diana Titik (Universitas Batam, 2021)
This study aims to determine the effect of service quality, customer value, and Customer Relationship Management on customer loyalty at JNE Express Plamo Garden. The method used in this study is a quantitative method. The population in this study was JNE Express Plamo Garden customers in January and February 2022 with a total of 49,620 people. The sample in this study was 100 respondents. The data collection technique used in this study was a questionnaire / questionnaire that was tested for validity and reliability. Data analysis techniques use Multiple Linear Regression, Classical Assumption Test, Hypothesis Test (t Test and F Test) and Coefficient of Determination. Data processing in this study used the SPSS Software version 25 program. The results of this study show that Service Quality has a positive and significant effect on Customer Loyalty at JNE Express Plamo Garden with a probability value of 0.000 < 0.05. Customer Value has a positive and significant effect on Customer Loyalty at JNE Express Plamo Garden with a probability value of 0.002<0.05. Customer Relationship Management (CRM) has a positive and significant effect on Customer Loyalty at JNE Express Plamo Garden with a probability value of 0.033<0.05. The coefficient of determination of 49.9% shows the contribution of Service Quality, Customer Value, and Customer Relationship Management (CRM) to Customer Loyalty at JNE Express Plamo Garden and the remaining 50.1% is explained by various other variables.